Child-Friendly Justice – Croatian Perspective - Kunda, Ivana; Smojver, Martina (Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective, 2025)
Abstract:The level of ‘child-friendliness’ of justice systems in different countries may greatly vary. In Croatia, rights of the child are guaranteed under the Constitution of the Republic of Croatia. In addition, a great deal of provisions ensuring rights of children in civil, criminal and administrative court proceedings may be found in different legal acts. These rules only add to the broader framework provided by the relevant supranational instruments. Irrespective of the many benefits this system has for children, there is still room for improvement in practice by introducing new communication methods and technical means, as well as continuous education. This national report provides an overview of the general legislative framework on the participation and the rights of the child in proceedings before the courts in Croatia. In addition to the general rules provided by international and EU instruments, as well as the Constitution, it details the existing rules on the participation of children in civil, criminal and administrative proceedings before courts. Additionally, it offers a glimpse into other ways of promoting children’s rights of participation in Croatia, particularly through different activities of the Office of the Ombudsman for Children.Keywords: rights of the child; participation of children in court proceedings; civil court proceedings; criminal court proceedings; administrative court proceedings